Electromagnetics : with applications - Kraus, John Daniel, 1910- (McGraw-Hill series in electrical and computer engineering., 1999)
Introduction; Electric and magnetic fields; Transmission lines; Wave propagation, attenuation, polarization, reflection, refraction and diffraction; Antennas, radiation, and wireless systems; Electrodynamics; Dielectric and magnetic materials; Waveguides, resonators, and fiber optics; Bioelectromagnetics; Electromagnetic effects in high-speed digital systems; Numerical methods.